Prioritization and Ranking of Phases for the Management of the Construction Project of the LNG Plant Production Line - R. Yu. Dashkov (Модернизация, инновация, развитие)
Purpose: the main purpose of this article is to explore the feasibility of using the ISM-Interpretive Structural Modeling method to prioritize the phases in the management of the LNG plant construction project. To achieve this goal, the following tasks must be solved in the article: identify the phases of the project at the planning stage that affect the Final Investment Decision (FID); draw up a reachability matrix that defines the interrelations between the phases of the project; split the phases of the project into hierarchical levels; construct a directed graph model and a diagram of the degree of influence and coherence of the project phases facilitating the adoption of strategic management decisions and the coordination of internal and external stakeholders. Methods: this article is based on the concept of project management and complex systems, which can be investigated using the Interpretive Structural Modeling method, with reference to the specifics of LNG plants. Results: the phases of the project were identified and the relationships between them in the planning phase influencing the FID were established. As a result of modeling, the phases of the project were aligned in a hierarchical structure of the directed graph and positioned on the influence and connectivity diagram, which allows the Project Office of the company to correctly determine priorities in coordination of project participants. Conclusions and Relevance: the present studies show that the method of Interpretive Structural Modeling is effective in identifying and modeling complex relationships between the phases of the project, as a result of which it is possible to build a strategy for the adoption of the Final Investment Decision. This methodology can be extended to subsequent stages of the project. Project managers can prioritize and rank the phases of the project by levels to make effective management decisions to improve the coordination of internal and external stakeholders involved in the implementation of this project. The practical application of the results will improve the management processes between the Project Office and company departments and external stakeholders.